HUKUMAN KEBIRI TERHADAP PELAKU KEKERASAN SEKSUAL PADA ANAK (PEDOFILIA) DALAM PERSPEKTIF HUKUM ISLAM - Asri Khumairoh (YUDISIA : Jurnal Pemikiran Hukum dan Hukum Islam, 2018)
Sexual crime of chlidren in Indonesia increased every year.  So thatgovernment  take out Perppu Number 1 year 2016 and determined tobe Law Number 17 Year 2016 that applied punishment for a sexualoffender by imposing chemically castrated. While in Islam the practiceof castration are forbidden. So it takes about religious views as on formof enlightenment and consideration to decide and formulate thingsespecially in national criminal law. Based on the description,formulation problem to deduce and know in this research is: whychemicall castrartion choose as a sanction again pedophile actor?How does review Islamic law to be  chemical castrartion againpedophile actor? Research methods used is deskriptif. The techniquesused to collec data is librarianship study. Based on the results of thestudy: first, reason the government choose chemical castrartion againpedophile actor because chemical castrartion can reduce sexual driveperson. Process crastation can do when the sexual offender in prison,so that sexual offender take out in prison will return to normal. Second,castration in Islam with cutting procedure, indicated not tio marry andnot as apenalty. The practice oe chemical crastation or punishment forpedophile actors is allowed.